GAGASAN GAYA MANAJEMEN INDONESIA - Handayanto, Eko (Journal of Innovation in Business and Economics, 2011)
The  Indonesia management idea didn’t separate from management thought itself. If we look from the geographical aspect, Indonesia is near eastern managemen style, but empirical evidence shows a western orientation practice. There is an organizational culture dispute and it has an influence toward the organizational output to be solved. The alternative solution is to integrate both of  management style within local culture. This integration needs to adjust with Indonesian culture to optimize the organizational performance.The Indonesian management style must put emphasis on distinctive local uniqueness along with the influence from both east and west